2019
DOI: 10.1177/1028315319887389
|View full text |Cite
|
Sign up to set email alerts
|

Duration Matters: Separating the Impact of Depth and Duration in Study Abroad Programs

Abstract: Study abroad participation has increased dramatically over the past two decades, primarily through the growth of short-term study abroad experiences. Given this, it is logical to ask whether short-term experiences are capable of delivering student learning outcomes equivalent to those of long-term experiences. The research presented in this article addresses this question by asking if program duration (i.e., temporal length of the academic program) or depth (i.e., focused and reflective interaction with the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Further, thoughtful and deliberate programming to provide cross-cultural experiences may go a long way when integrated into the exchange student experience such as International Student Organizations as they merge on-campus integration strategies with the types of experiences that students desire to have, especially when exchange periods are fairly short compared to degree-seeking students. Exchange students may not have the time to develop relationships or to invest in the activities that foster the intercultural aspects of student exchanges due to the limited time available (DeLoach et al, 2019). Additionally, other national governments might consider mimicking a "K-pop Model" by investing in the promotion of their popular entertainment media as a strategy to attract future exchange students, as has been in the case in Korea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, thoughtful and deliberate programming to provide cross-cultural experiences may go a long way when integrated into the exchange student experience such as International Student Organizations as they merge on-campus integration strategies with the types of experiences that students desire to have, especially when exchange periods are fairly short compared to degree-seeking students. Exchange students may not have the time to develop relationships or to invest in the activities that foster the intercultural aspects of student exchanges due to the limited time available (DeLoach et al, 2019). Additionally, other national governments might consider mimicking a "K-pop Model" by investing in the promotion of their popular entertainment media as a strategy to attract future exchange students, as has been in the case in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between "international students" and other potential classifications of face-to-face (and even distance) students has often been unclear in the academic literature (Kozmützky & Putty, 2016;Madge et al, 2015;Rensimer, 2016;Stewart, 2019). While there are numerous ways to achieve cross-border education by conventional movement, where students move to the location of the university (Beech, 2015) or transnational education where agents of the university move to the location of the students (Francois, 2016), exchange students' mobility is characterized by temporary/short term sojourns and credit mobility (DeLoach et al, 2019;Perez-Encinas & Ammigan, 2016). On the one hand, traditional reciprocal academic exchanges are enabled via bilateral and/or multilateral consortium agreements (e.g., ERASMUS, CONASEP, UMAP, CAMPUS Asia), whereas non-reciprocal academic exchanges enroll tuition paying exchange students directly and are often termed "study abroad" (or visiting students in Korea).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative studies have found generally more positive academic, personal, intercultural, and career development outcomes for participants of longer-term programs abroad than shorter-term ones, but short-term students often make comparable gains in specific outcomes within larger outcome domains (DeLoach, Kurt, & Olitsky, 2019;Dwyer, 2004;Medina-López-Portillo, 2004;Vande Berg et al, 2009). Dwyer ( 2004) credited this variation to the impact that a well-planned, intensive short-term program can provide.…”
Section: Short-term Programs and Compressed-format Coursesmentioning
confidence: 99%
“…For some, study abroad is a highimpact learning experience for helping students achieve these outcomes (Kuh, 2008). Previous research (Arendale & Hane, 2014;Buckley, 2015;DeLoach et al, 2019;Statham, 2015) has focused on how aspects of study abroad effect student learning without fully accounting for the on-campus experiences students bring with them when they embark for study abroad. As the number of U.S. students studying abroad grows nearly every year (Institute of International Education, 2019a), it is important to explore outcomes, such as intrapersonal development, through a context that accounts for experiences before and during their time abroad.…”
Section: Significancementioning
confidence: 99%